2013
DOI: 10.1177/0194599813496044a55
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional, Virtual Technologies and Haptic Simulation Temporal Bone Surgical Training

Abstract: Poster Presentations P159Methods: Retrospective review of non-randomized prospectively maintained patient databases at two tertiary centers from 1998-2008; Sahlgrenska University Hospital (SU) in Gothenburg, Sweden, and Aberdeen Royal Infirmary (ARI) in Aberdeen, Scotland. Patients with stage III and IV disease were included in the study. Primary outcome measures included 3-year overall and disease-specific survival depending on treatment.Results: A total of 176 patients were identified, of whom 83% were male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The remaining studies utilized quasi-experimental methodologies (7 studies, 13.73%). Notably, our review found 17 RCTs 38,41,49,50,54,55,58,65,6769,77,78,8184 that were not included in the previous review, 11 of which were published before 2019 38,41,49,50,54,55,58,65,6769 and the rest being novel studies. 77,78,8184…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The remaining studies utilized quasi-experimental methodologies (7 studies, 13.73%). Notably, our review found 17 RCTs 38,41,49,50,54,55,58,65,6769,77,78,8184 that were not included in the previous review, 11 of which were published before 2019 38,41,49,50,54,55,58,65,6769 and the rest being novel studies. 77,78,8184…”
Section: Resultsmentioning
confidence: 97%
“…Notably, our review found 17 RCTs 38,41,49,50,54,55,58,65,[67][68][69]77,78,[81][82][83][84] that were not included in the previous review, 11 of which were published before 2019 38,41,49,50,54,55,58,65,[67][68][69] and the rest being novel studies. 77,78,[81][82][83][84] The most common population sampled were medical residents (14 studies), followed by novices (9 studies), physicians (8 studies), and medical students (7 studies).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations